Omeprazole-clopidogrel interaction and neurovascular complications after flow-diverter device placement. (3rd June 2021) - Catapano, Joshua S; Srinivasan, Visish M; Wakim, Andre A; Lundberg, Jaclyn N; Rutledge, Caleb; Cole, Tyler S; Baranoski, Jacob F; Fredrickson, Vance L; Rahmani, Redi; Albuquerque, Felipe C; Ducruet, Andrew F
Abstract : Background: Omeprazole is a common proton pump inhibitor that interferes with the hepatic activation of clopidogrel and potentially reduces its platelet-inhibitory effect. Omeprazole has been shown to increase P2Y12 levels and adverse cardiovascular outcomes in patients treated with drug-eluting stents. However, omeprazole use among patients treated with flow-diverting stents for intracranial aneurysms has not been evaluated. Methods: All patients with placement of a flow-diverting device for treatment of an intracranial aneurysm at a tertiary institution from January 1, 2014, to December 31, 2018, were retrospectively analyzed. Inclusion criteria included documented clopidogrel administration, available P2Y12 levels, and thorough documentation of administration of other medications, including omeprazole. Results: A total of 138 patients met the inclusion criteria. Sixteen patients (12%) were receiving omeprazole and clopidogrel at treatment. P2Y12 reactivity was significantly greater in the omeprazole cohort (mean P2Y12 level, 250 P2Y12 reaction units (PRU)) than in the control cohort (mean P2Y12 level, 112PRU) (P<0.001). Furthermore, a greater proportion of patients had a P2Y12 level >180 PRU in the omeprazole cohort (14 of 16 [88%] vs 24 of 122 [20%]; P<0.001; OR [95% CI], 29 [6–134]). Conclusion: Omeprazole was associated with a significant increase in the mean P2Y12 reactivity level among patients with intracranial aneurysms treated with flow-diverting devices who received clopidogrel. However, receipt of omeprazole was not associated with an increased risk of ischemic events or stent stenosis. For neuroendovascular patients who are treated with a flow diverter while receiving clopidogrel, alternative gastrointestinal medication regimens should be considered.